Purifying Crude Glycerol from Biodiesel Production for Sustainable Energy Solutions - Rahman, Herliati (Jurnal Teknologi, 2023)
Biodiesel production has been an important part of a global effort to replace fossil fuels with renewable energy sources. However, one of the problems facing biodiesel production is increased production of glycerol as a by-product. Glycerol, or crude glycerol (CG), is generally produced in significant quantities and needs to be managed wisely. This article discusses the potential use of glycerol from biodiesel production as a raw material for bioethanol production. By optimizing fermentation processes, genetic engineering technology, and purification, glycerol can be converted into bioethanol, one of the more environmentally friendly renewable fuels. The success of the conversion of glycerol to bioethanol is also supported by advances in genetic engineering technology that enable the development of more efficient and productive microorganisms. This creates great opportunities to reduce waste, support resource sustainability, and reduce dependence on fossil fuels through the use of glycerol as a bioethanol raw material. Conversion of glycerol to bioethanol is a step towards more sustainable and environmentally friendly renewable energy.